Effects of short-term core stability training on dynamic balance and trunk muscle endurance in novice olympic weightlifters - Szafraniec, R.; Bartkowski, J.; Kawczynski, A. (Journal of Human Kinetics, 2020)
Our primary objective was to investigate the effects of short-term core stability training on dynamic balance and trunk muscle endurance in novice weightlifters learning the technique of the Olympic lifts. Our secondary objective was to compare dynamic balance and trunk muscle endurance between novice and experienced weightlifters. Thirty novice (NOV) and five experienced (EXP) weightlifters participated in the study. Mediolateral (ML) and anteroposterior (AP) dynamic balance and trunk muscle endurance testing were performed a week before (Pre) and after (Post) a 4-week core stability training program. In the NOV group, there was an improvement of both dynamic balance (ML and AP, p = 0.0002) and trunk muscle endurance (p = 0.0002). In the EXP group, there was no significant difference between Pre and Post testing conditions, except an increase in muscle endurance in the right-side plank (p = 0.0486). Analysis of the results showed that experienced lifters were characterized by more effective dynamic balance and greater core muscle endurance than their novice peers, not only before the training program but after its completion as well. In conclusion, the applied short-term core stability training improved dynamic balance and trunk muscle endurance in novice weightlifters learning the Olympic lifts. Such an exercise program can be incorporated into a training regime of novice weightlifters to prepare them for technically difficult tasks of the Olympic snatch and clean and jerk.